2014
DOI: 10.1074/jbc.m114.602243
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide (CO) Is a Novel Inhibitor of Connexin Hemichannels

Abstract: Background: Carbon monoxide and connexin hemichannels are involved in several physiological and pathological processes. Results: Carbon monoxide inhibits Cx43 and Cx46 hemichannel opening. Conclusion: Connexin hemichannels are modulated by gaseous transmitters. Significance: Our observations will help understand the effects of CO and CO donors in pathological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Thus, we hypothesized that both intracellular and extracellular Cys control some hemichannel properties by changing their redox status (Figure 2 ). Accordingly, carbon monoxide (CO), which is another gaseous transmitter that modulates the redox status in cells, induced an important current reduction of Cx46 hemichannels (León-Paravic et al, 2014 ). This effect was observed in Xenopus laevis oocytes expressing a Cx46 mutant lacking intracellular Cys (Cx46C3A), but was absent in oocytes expressing a Cx46 Cys-lacking mutant (Cx46CL), suggesting that extracellular Cys is/are important(s) for the inhibition of Cx46 hemichannels induced by CO.…”
Section: Extracellular Vs Intracellular Connexin Cysteines: Their Romentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we hypothesized that both intracellular and extracellular Cys control some hemichannel properties by changing their redox status (Figure 2 ). Accordingly, carbon monoxide (CO), which is another gaseous transmitter that modulates the redox status in cells, induced an important current reduction of Cx46 hemichannels (León-Paravic et al, 2014 ). This effect was observed in Xenopus laevis oocytes expressing a Cx46 mutant lacking intracellular Cys (Cx46C3A), but was absent in oocytes expressing a Cx46 Cys-lacking mutant (Cx46CL), suggesting that extracellular Cys is/are important(s) for the inhibition of Cx46 hemichannels induced by CO.…”
Section: Extracellular Vs Intracellular Connexin Cysteines: Their Romentioning
confidence: 99%
“…Interestingly, current evidence allows us to suggest that there is a pool of hemichannels at the plasma membrane with reduced extracellular Cys, which allows them to open frequently. When these reduced Cys become oxidized (e.g., forming disulfide bonds or carbonylated; León-Paravic et al, 2014 ), hemichannels become mostly closed. Green dots represent Cys oxidized by free radicals such as ROS, RNS or carbon monoxide (CO).…”
Section: Extracellular Vs Intracellular Connexin Cysteines: Their Romentioning
confidence: 99%
See 1 more Smart Citation
“…; ref. ). León‐Paravic et al showed that a CO donor (CORM‐2) induced a dose‐response inhibition in Cx46 hemichannels expressed in Xenopus laevis oocytes.…”
Section: Carbon Monoxide Modulates CX Hemichannelsmentioning
confidence: 97%
“…In general terms, an increase of CO concentration has been associated to protective cellular effects , whereas increases in NO concentration have been associated to deleterious effects . According to this, the addition of NO donors to astrocytes in culture induces a massive Cx43 hemichannel opening ; however, when a CO donor is added to HeLa cells, Cx43 hemichannel became closed . However, it is unknown whether astrocytes exposed to CO donors also close their Cx43 hemichannels, and whether the effect of NO and CO over Cx43 hemichannels is synergic or antagonic is also unknown.…”
Section: Possible Interplay Between Co and No In CX Hemichannel Activitymentioning
confidence: 99%